39. Impact of Antimicrobial Stewardship Interventions in a Community Hospital setting: An Interrupted Times Analysis. (4th December 2021) - Li, Jason; Chan, Ken; Parvez, Hina; Gorlin, Margaret; Smith, Miriam A
Abstract: Background: Community hospitals have fewer resources for antimicrobial stewardship programs (ASP) compared to larger tertiary hospitals. At our 312-bed community hospital, Long Island Jewish Forest Hills/Northwell, a combination of modified preauthorization, prospective audit feedback, and ASP education was implemented starting in August 2019 (Monday through Friday 9 am to 5 pm). Methods: This retrospective study evaluated the impact of ASP interventions on the rate of targeted antimicrobial use over a 7 month pre- vs 7 month post- intervention period (Aug 2018 to Feb 2019 vs Aug 2019 to Feb 2020). Targeted antimicrobials included piperacillin-tazobactam, vancomycin, daptomycin, and carbapenems. The primary outcome was the monthly mean for overall targeted antimicrobial use measured by the rate of antimicrobial days per 1000 days present. Secondary outcomes were the individual rates of antimicrobial days per 1000 days present for each of the targeted antimicrobials, and the hospital's overall standardized antimicrobial administration ratio (SAAR). Data were analyzed as a segmented regression of interrupted time series. Results: Pre-intervention, there was an increasing trend (positive slope, p< 0.05) in the monthly mean, hospital SAAR, vancomycin and piperacillin-tazobactam use. Post-intervention, there was a significant change in slope for these same metrics, indicating a decrease in the mean use. Immediate impact of ASP interventions, measured by the difference in antibiotic use between the end of each intervention period, was visually evident in all cases except carbapenems (Fig. 1 through 4). The immediate impact on the overall monthly mean represented a significant reduction in the rate of antimicrobial days per 1000 days present, -12.72 (CI -21.02 to -4.42, P < 0.0066). The pre- vs post- ASP gap for all measures was negative and consistent with fewer days of antibiotic use immediately following intervention. Conclusion: A targeted, multifaceted ASP intervention utilizing modified preauthorization, prospective audit feedback, and education significantly reduced antibiotic use in a community hospital. Disclosures: All Authors : No reported disclosures